O-021 Validation of the delayed functional improvement after neurothrombectomy (DEFIANT) score in the tiger study. (23rd July 2022) - Desai, S; Jha, R; Catapano, J; Gupta, R; Saver, J; Levy, E; Zaidat, O; Yavagal, D; Jadhav, A
Abstract : Background: Delayed functional independence (DFI) in patients who do not experience early improvement after endovascular thrombectomy (EVT) is commonly observed in clinical practice. Recent studies suggest that the rate of DFI is approximately 30%. Younger age, lower discharge NIHSS score, and absence of any hemorrhage are independent predictors of DFI. We aim to validate the recently reported DEFIANT score to predict delayed functional improvement in the TIGER Study. Methods: Demographic, clinical, radiological, treatment, and procedural information were analyzed from Tiger Trial (patients with complete data and undergoing EVT for anterior circulation LVO). Incidence of delayed functional independence (DFI, mRS score 0–2 at 90 days in non-EFI patients) was analyzed and the DEFIANT score was validated in the TIGER study. The DEFIANT score incorporates age, discharge NIHSS score, and presence/absence of any hemorrhage at discharge (Online calculator: https://bit.ly/3KZRVq5) probability of DFI= e (3.9699 – (.0359 * age) – (.2276*discharge NIHSS) – (.6013*hemorrhage) /[1 + e 3.9699 – (.0359 * age) – (.2276*discharge NIHSS) – (.6013 *hemorrhage) ] Results: A total of 137 patients met study criteria. DFI was observed in 38% (30/79) of non-early improvers (79/137). Receiver operating curves for the DEFIANT score showed a robust capacity to predict delayed functional independence (using optimal cut-off of 0.42 for predicting DFI) ( figure 1 : area under the curve 0.775). The DEFIANT score had sensitivity 69%, specificity 86%, positive predictive value 74%, and negative predictive value 87% for detecting DFI. If the TIGER study had stopped follow-up for outcomes at discharge and used the DEFIANT score, rate of predicted 90-day mRS 0–2 would be similar to actually observed 90-day mRS 0–2 (60.5% vs 61.3%, p=0.90). Conclusion: The DEFIANT score, utilizing readily available variables such as age, discharge NIHSS score, and presence/absence of any hemorrhage, is a reliable tool to predict the probability of delayed functional independence after stroke thrombectomy. Disclosures: S. Desai: None. R. Jha: None. J. Catapano: None. R. Gupta: None. J. Saver: None. E. Levy: None. O. Zaidat: None. D. Yavagal: None. A. Jadhav: None.